Contested experiences and potential justice at the limit of the law for poor urban children in Bangladesh - Sergei Shubin (Children's Geographies, 2019)
The paper re-examines the ways in which boundaries for naming poor delinquent children are drawn in the Bangladeshi legal system. The paper questions the use of the term “delinquent” children, their position and “diversion” from crime. It draws on the works of Georges Bataille to question the boundaries of an isolated child as a stable and dependent entity in the law and exposes the limit as a point of passage and proximity with others as a part of being-in-common. Drawing on the interviews with "delinquent" children, it challenges the logic of un/reason used to draw the limits of normality in the legal discourse. Furthermore, it questiones the ethical boundaries of calculative rationality applied to poor children in Bangladesh, and seeks out possibilities for community and justice at the limit of the law